Active magnetic regenerative refrigeration using superconducting solenoid for hydrogen liquefaction. (1st January 2022) - Kamiya, Koji; Matsumoto, Koichi; Numazawa, Takenori; Masuyama, Shinji; Takeya, Hiroyuki; Saito, Akiko T.; Kumazawa, Naoya; Futatsuka, Kazumi; Matsunaga, Keigo; Shirai, Tsuyoshi; Takada, Suguru; Iida, Teruhito
Abstract: A magnetic refrigerator that makes use of the magneto-caloric effect realizes a highly efficient cooling device. Since the cooling power of magnetic refrigerators depends largely on the strength of the magnetic field, the use of a superconducting magnet is essential. Using magnetic refrigeration, achieving a liquefaction efficiency of larger than 50% is theoretically possible, which is twice that of conventional gas expansion refrigerators. In this study, an active magnetic regenerative refrigerator, one of the magnetic refrigerators using a superconducting solenoid, was built and hydrogen liquefaction was successfully demonstrated.